Civic responsibility in drug prevention: a study from social networks - Leiva Díaz, Viriam (2014)
Background: the aim of this article presents the results of the study on civic responsibility in preventing drug phenomenon, this being an active and supportive participation of each of the members of the Costa Rican society, research was exploratory under the quantitative approach of cross section.Method: the population consisted of 353 people registered inhabitants of Costa Rica on the social network Facebook. To collect the data generating way to survey questions on that page were used.Result: Among the findings it can be mentioned that participants know all the aspects that are embedded in the concept of civic responsibility, however, there is a great escape, by the people, to this in terms of drug prevention.Conclusion: The participants do not exercise their civic responsibility through ignorance, whether of law or public policy, delegating that responsibility to different entities, individuals or institutions.